PERANCANGAN DAN PEMBUATAN PROTOTYPE TURBIN KAPLAN UNTUK SKALA PEMBANGKIT LISTRIK TENAGA MIKROHIDRO (PLTMH) - Cristopher Bangun, Arya; Arta Wijaya, I Wayan; Budiastra, I Nyoman (Jurnal SPEKTRUM; Vol 12 No 1 (2025): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2025.v12.i01.p13, 2025)
A Micro-Hydro Power Plant (MHPP) is a small-scale power generator driven by water, utilizing the height (water head) of a waterfall and the volume of discharged water. The MHPP is designed by determining dimensions using formulas from relevant articles and journals. Once the necessary tools and materials are identified, they are assembled into an MHPP prototype with an axial-flow propeller turbine. The design specifications of the paddle turbine prototype include a head height of 2 meters, an intake pipe diameter of 2.5 mm, a flow rate of 0.019 cubic meters per second, 30 blades, an opening angle of 30°, a blade length of 0.07 meters, a width of 0.05 meters, an inner diameter of 0.25 meters, and an outer diameter of 0.45 meters. The prototype features a total of five driving blades with an outer diameter of 0.20 meters, a journal diameter of 0.06 meters, and a runner width of 0.07 meters. The rotor turbine prototype was tested and produced a power output of 6.08 watts with an efficiency of 25.3% .